Satire in African Letters: Black Appraisals of White Ethnologists in the Works of Ferdinand Oyono, Tchicaya U'Tam'si and Yambo Ouloguem - Ingeborg M. Kohn (Studies in 20th & 21st Century Literature, 1980)
Among the black African writers who have singled out whites for satirical treatment, the novelists Ferdinand Oyono and Yambo Ouologuem and the poet Tchicaya U'Tam'si have focused on a certain type of ethnologist: the man who has come in the guise of explorer and scientist, but whose prejudices, ignorance, greed, presumptuousness and other negative characteristics are soon unmasked by his native hosts. In their works, we find portraits depicting the white ethnologist that are not only unanimous expressions of scorn and contempt, but also examples of the skillfull use of satire as a literary weapon.
Keywords: black African writers; Ferdinand Oyono; Yambo Ouologuem; Tchicaya U' Tam' si; ethnology; white ethnologist; racism; ignorance; scientist; greed; presumptuousness; native hosts; satire; prejudice